SUMBER RISIKO DAN MITIGASI RISIKO JAMUR MERANG (Volvariella volvaceae) DI KECAMATAN JATISARI KABUPATEN KARAWANG - Siti Sarah Melani; Lies Sulistyowati; Lucyana Trimo (Universitas Galuh Ciamis, 2021)
Mushroom is one of the leading vegetable commodities in Karawang Regency. The consumption growth of this mushroom commodity always increases every year. Risk is an opportunity for an event to occur that can be measured by decision makers. The purpose of this study is to identify mitigation and risk mapping that occurs in mushroom farming in Jatisari District, Karawang Regency. Data analysis used descriptive quantitative and House of Risk (HOR). The location of this study is in Jatisari District, Karawang Regency, that Jatisari District, Karawang Regency is a sub-district where members of the farmer group have the highest mushroom cultivation business. The data used are primary data and secondary data obtained from agencies related to mushroom farming. Based on the results of the study, the sources (agents) of risk in mushroom farming that have occurred in the last few seasons and have the potential to reappear in the future, are: (1) Lack of capital for mushroom farming, (2) The selling price of edible mushroom fluctuates, (3) The price of edible mushroom at the middleman level is lower than the market level. Alternative risk mitigation actions that can be taken by farmers include: (1) The government helps capitalize on mushroom farming and other institutions, (2) Facilitates the disbursement process in banking through FGDs with financial institutions, (3) Conducts training on financial management in farming.